Влияние металлов на фото- и термостимулированные превращения в йодиде висмута - Устинова Л. Н.; Шустов М. А. Михаил Анатольевич; Суровой Э. П.; Федорченко Е. Н. (Томск, 1984)
Деп. в ОНИИТЭХИМ, г. Черкассы, 21.06.84, № 590хп-Д84